Inhibition of PI3K signaling triggered apoptotic potential of curcumin which is hindered by Bcl-2 through activation of autophagy in MCF-7 cells - Akkoç, Yunus; Berrak, Özge; Çoker Gürkan, Ajda; Palavan Ünsal, Zeynep Narçın; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN (Elsevier France-Editions Scientifiques Medicales Elsevier, 23 Rue Linois, 75724 Paris, France, 2015)
Curcumin is a natural anti-cancer agent derived from turmeric (Curcuma longa). Curcumin triggers intrinsic apoptotic cell death by activating mitochondrial permeabilization due to the altered expression of pro-and anti-apoptotic Bcl-2 family members. Phosphoinositol-3-kinase (PI3K) and Akt, key molecular players in the survival mechanism, have been shown to be associated with the Bcl-2 signaling cascade; therefore, evaluating the therapeutic efficiency of drugs that target both survival and the apoptosis mechanism has gained importance in cancer therapy. We found that Bcl-2 overexpression is a limiting factor for curcumin-induced apoptosis in highly metastatic MCF-7 breast cancer cells. Forced overexpression of Bcl-2 also blocked curcumin-induced autophagy in MCF-7 cells, through its inhibitory interactions with Beclin-1. Pre-treatment of PI3K inhibitor LY294002 enhanced curcumin-induced cell death, apoptosis, and autophagy via modulating the expression of Bcl-2 family members and autophagosome formation in MCF-7 breast cancer cells. Atg7 silencing further increased apoptotic potential of curcumin in the presence or absence of LY294002 in wt and Bcl-2+ MCF-7 cells. The findings of this study support the hypothesis that blocking the PI3K/Akt pathway may further increased curcumin-induced apoptosis and overcome forced Bcl-2 expression level mediated autophagic responses against curcumin treatment in MCF-7 cells. (C) 2015 Elsevier Masson SAS. All rights reserved.
Keywords: Curcumin; Breast cancer; Apoptosis; PI3K; LY294002; Colon-cancer cells; Down-regulation; Breast-cancer; Chemotherapeutic Drugs; Family-members; Leukemia-cells; Kappa-B; Death; Expression; Pathways